2020
DOI: 10.1039/d0ra01277g
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of the competitive adsorption in 8-methylquinoline hydrogenation over a Ru catalyst

Abstract: The stronger adsorption of 8-MQL hampers further adsorption of 4H-8-MQL, which results in the difficulty in 10H-8-MQL production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Impressive achievements have been reached in this area by applying catalysts based on noble metal NPs (e.g., Pd, Pt, Rh, , Ru, , Ir, ,, and Au , ). However, the high and volatile price associated with the low availability of precious metals has boosted the interest to exploit cheap and earth-abundant metals for the development of novel catalysts in recent times, although, to date, to a limited extent for the hydrogenation of quinolines.…”
Section: Introductionmentioning
confidence: 99%
“…Impressive achievements have been reached in this area by applying catalysts based on noble metal NPs (e.g., Pd, Pt, Rh, , Ru, , Ir, ,, and Au , ). However, the high and volatile price associated with the low availability of precious metals has boosted the interest to exploit cheap and earth-abundant metals for the development of novel catalysts in recent times, although, to date, to a limited extent for the hydrogenation of quinolines.…”
Section: Introductionmentioning
confidence: 99%
“…In this class of novel heterocyclic molecules, carbazole-based molecules, such as N -ethylcarbazole and N -propylcarbazole, are the earliest new LOHCs that can completely realize hydrogenation and dehydrogenation below 200 °C. The hydrogenation and dehydrogenation processes of carbazole-based molecules have been widely studied over different catalysts. , Subsequently, quinoline and indole molecules have also been developed as new LOHCs. Carbazole, quinoline, and indole are all N-heterocyclic compounds, but their N-electron structures differ significantly.…”
Section: Introductionmentioning
confidence: 99%
“…However, Dong et al observed that the strong electronegativity of the N atoms in 8-methylquinoline (8-MQL) may irreversibly adsorb on metal surfaces, leading to catalyst poisoning and favoring the production of 100% 4H-8-methylquinoline. 20 To modulate the charge density of the N atom in the quinoline (QL) molecule and consequently control the adsorption strength of QL on the catalyst surface, we strategically positioned a methyl group at various locations within the QL molecule, thereby altering the steric hindrance. We compared the enthalpy of hydrogenation and theoretical dehydrogenation temperatures under varying hydrogen partial pressures for QL, 2-MQL, 6-MQL, and 8-MQL.…”
mentioning
confidence: 99%